Exploring the Putative Involvement of MALAT1 in Mediating the Beneficial Effect of Exendin-4 on Oleic Acid-Induced Lipid Accumulation in HepG2 Cells - Olfa Khalifa; Sama Ayoub; Abdelilah Arredouani (Biomedicines)
Background/Objectives: The reduction of oleic acid (OA)-induced steatosis in HepG2 cells observed upon treatment with the glucagon-like peptide-1 receptor agonist (GLP-1RA) Exendin-4 (Ex-4) is associated with the modulation of the expression of several microRNAs, long non-coding RNAs (lncRNAs), and mRNAs. Notably, MALAT1, an lncRNA, shows significant downregulation in the presence of Ex-4 as compared to OA alone. In this study, we aimed to explore the role of MALAT1 in the positive impact of Ex-4 on OA-induced lipid accumulation in HepG2 cells. Methods: Steatosis in HepG2 cells was induced by treating them with 400 µM OA. The effect of Ex-4 on steatosis was examined by treating the steatotic cells with 200 nM of EX-4 for 3 h. MALAT1 was silenced with siRNA, while gene expression was quantified using qRT-PCR. Results: In the presence of Ex-4, the silencing of MALAT1 did not exert any discernible influence on de novo lipogenesis genes such as PPARγ and SREBP1. However, MALAT1 silencing significantly affected, to varying degrees, the expression levels of several lipid metabolism genes such as FAS, ACADL, CPT1A, and MTTP. Conclusions: Further investigations are warranted to fully decipher the role of the Ex-4-MALAT1 in the positive impact of GLP-1RAs on steatosis.